4D Reconstruction and Identification of Carotid Artery Stenosis Utilizing a Novel Pulsatile Ultrasound Phantom. Issue 10 (22nd October 2021) - Thurgood, Harrison; Witte, Russell; Laksari, Kaveh
Abstract: As a major application focus of vascular ultrasonography, the carotid artery has long been the subject of phantom design and procedure focus. It is therefore important to devise procedures that are minimally invasive and informative, initially using a physiologically accurate anthropomorphic phantom to validate the methodology. In this article, a novel phantom design protocol is presented that enables the efficient production of a pulsatile ultrasound phantom consisting of soft and vascular tissue mimics, as well as a blood surrogate fluid. These components when combined give the phantom high acoustic compatibility and lifelike mechanical properties. The phantom was developed using "at‐home" purchasable components and 3D printing technology. The phantom was subsequently used to develop a 4D reconstruction algorithm of the pulsing vessel in MATLAB. In pattern with recent developments in medical imaging, the 4D reconstruction enables clinicians to view vessel wall motion in a 3D space without the need for manual intervention. The reconstruction algorithm also produces measured inner luminal areas and vessel wall thickness, providing further information relating to structural properties and stenosis, as well as elastic properties such as arterial stiffness, which could provide helpful markers for disease diagnosis. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Constructing a pulsatile ultrasound phantom model Support Protocol : Creating a vascular mimic mold Basic Protocol 2 : Creating a 4D reconstruction from ultrasound frames